KEPEMIMPINAN PEREMPUAN DALAM PEMERINTAHAN DESA (STUDY KASUS PEMERINTAH DESA TERARA KECAMATAN TERARA KABUPATEN LOMBOK TIMUR PERIODE TAHUN 2007-2012 - Dewita Harthanti (SOSIO EDUKASI Jurnal Studi Masyarakat dan Pendidikan, 2017)
The professional competence characterized teaching materials mastery,conducting educational study and be able to conduct the research subjects of sociology lesson planning to equip students to be able to carry out a good learning activities and educate in accordance with the intended learning objectives. The purpose of this paper is to examine the effectiveness of implementing learning model of scrambled group in increasing the students activity in the lesson planning study of sociology through lesson study. Students involved in the lesson study is the sixth semester students of sociology who are taking lesson planning study. The data on the effectiveness of implementing learning model of scrambled group in increasing the students activity had been analyzed by using interactive analysis, and proved that all of the students were more active by using scrambled group. At the first indicator of activity (asking questions), the students activity decreased 4%, the second indicator of activity (answering questions) increased 12%, the third indicator (thought/explanation), increased 46%. The indicator of activity of Listening and writing also increased respectively 35% and 69%. Collecting data used observation method using the observation sheet.